Evolutionary conservation of Y Chromosome ampliconic gene families despite extensive structural variation - Brashear, Wesley A.; Raudsepp, Terje; Murphy, William J. (Genome Research, 2018)
Despite claims that the mammalian Y Chromosome is on a path to extinction, comparative sequence analysis of primate Y Chromosomes has shown the decay of the ancestral single-copy genes has all but ceased in this eutherian lineage. The suite of single-copy Y-linked genes is highly conserved among the majority of eutherian Y Chromosomes due to strong purifying selection to retain dosage-sensitive genes. In contrast, the ampliconic regions of the Y Chromosome, which contain testis-specific genes that encode the majority of the transcripts on eutherian Y Chromosomes, are rapidly evolving and are thought to undergo species-specific turnover. However, ampliconic genes are known from only a handful of species, limiting insights into their long-term evolutionary dynamics. We used a clone-based sequencing approach employing both long- and short-read sequencing technologies to assemble ∼2.4 Mb of representative ampliconic sequence dispersed across the domestic cat Y Chromosome, and identified the major ampliconic gene families and repeat units. We analyzed fluorescence in situ hybridization, qPCR, and whole-genome sequence data from 20 cat species and revealed that ampliconic gene families are conserved across the cat family Felidae but show high transcript diversity, copy number variation, and structural rearrangement. Our analysis of ampliconic gene evolution unveils a complex pattern of long-term gene content stability despite extensive structural variation on a nonrecombining background.
10.1101/gr.237586.118